2005
DOI: 10.2174/1568009054863618
|View full text |Cite
|
Sign up to set email alerts
|

Purine Nucleoside Analogues for the Treatment of Hematological Malignancies: Pharmacology and Clinical Applications

Abstract: The purine nucleoside analogues (PNAs), fludarabine (FA), 2-CdA (2-chlorodeoxyadenosine, 2-CdA) and pentostatin (2'-deoxycoformycin, DCF) represent a group of cytotoxic agents with high activity in lymphoid and myeloid malignancies. PNAs share similar chemical structure and mechanism of action. Several mechanisms could be responsible for their cytotoxicity both in proliferating and quiescent cells, such as inhibition of DNA synthesis, inhibition of DNA repair and accumulation of DNA strand breaks. Induction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 183 publications
(282 reference statements)
0
52
0
1
Order By: Relevance
“…Although both cladribine and pentostatin are efficacious, the simplicity in dosing of cladribine coupled with its favorable toxicity profile, high percentage of complete remissions, and low incidence of relapse has earned it the first choice of treatment for HCL. Cladribine, like pentostatin, induces apoptosis by disrupting cellular metabolism through inhibition of DNA synthesis in both resting and dividing cells [54,55,60].…”
Section: Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Although both cladribine and pentostatin are efficacious, the simplicity in dosing of cladribine coupled with its favorable toxicity profile, high percentage of complete remissions, and low incidence of relapse has earned it the first choice of treatment for HCL. Cladribine, like pentostatin, induces apoptosis by disrupting cellular metabolism through inhibition of DNA synthesis in both resting and dividing cells [54,55,60].…”
Section: Treatmentmentioning
confidence: 99%
“…Although the purine analogues, including the newer fludarabine, share similar chemical structures and mechanisms of action, there is surprisingly little or no crossresistance among them [60,73,74]. In a study of 144 treated patients, Piro and coworkers [74] identified five patients who were either resistant to or intolerant of pentostatin.…”
Section: Drug Resistance Disease Relapse and Monitoring Mrdmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, deoxyadenosine-based analogues such as cladribine and fludarabine ( Figure 1) have both been shown to be active against various forms of leukemias and lymphomas (reviewed in [1]). Clofarabine, a second generation chemotherapeutic agent developed following the effectiveness of fludarabine, is active against several hematological malignancies, including acute and chronic leukemias (reviewed in [2]), myelodysplastic syndromes [3], and advanced pediatric acute leukemias [4].…”
Section: Introductionmentioning
confidence: 99%
“…TUB é de estrutura muito similar a da adenosina (Zimmerman et al, 1978), o que possibilita sua incorporação no ácido nucléico de microrganismos e células mamíferas. Porém é responsável por vários efeitos citotóxicos, como inibição da síntese de DNA, inibição do reparo de DNA e acúmulo na fita de DNA (Robak et al, 2005).…”
Section: Metabolismo De Purinasunclassified